Conference – 2015 Equation (1)

i j θ i P i = P ¯ j + i j ( θ i θ ¯ j ) ( P i P ¯ j ) MathType@MTEF@5@5@+= feaagKart1ev2aaatCvAUfeBSjuyZL2yd9gzLbvyNv2CaerbuLwBLn hiov2DGi1BTfMBaeXatLxBI9gBaerbd9wDYLwzYbItLDharqqtubsr 4rNCHbGeaGqiVu0Je9sqqrpepC0xbbL8F4rqqrFfpeea0xe9Lq=Jc9 vqaqpepm0xbba9pwe9Q8fs0=yqaqpepae9pg0FirpepeKkFr0xfr=x fr=xb9adbaqaaeGaciGaaiaabeqaamaabaabaaGcbaWaaabeaeaacq aH4oqCdaWgaaWcbaGaamyAaaqabaGccaWGqbWaaSbaaSqaaiaadMga aeqaaaqaaiaadMgacqGHiiIZcaWGQbaabeqdcqGHris5aOGaeyypa0 JabmiuayaaraWaaSbaaSqaaiaadQgaaeqaaOGaey4kaSYaaabeaeaa daqadaqaaiabeI7aXnaaBaaaleaacaWGPbaabeaakiabgkHiTiqbeI 7aXzaaraWaaSbaaSqaaiaadQgaaeqaaaGccaGLOaGaayzkaaWaaeWa aeaacaWGqbWaaSbaaSqaaiaadMgaaeqaaOGaeyOeI0Iabmiuayaara WaaSbaaSqaaiaadQgaaeqaaaGccaGLOaGaayzkaaaaleaacaWGPbGa eyicI4SaamOAaaqab0GaeyyeIuoaaaa@5804@